-X+3=7-X

Simple and best practice solution for -X+3=7-X equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -X+3=7-X equation:


Simplifying
-1X + 3 = 7 + -1X

Reorder the terms:
3 + -1X = 7 + -1X

Add 'X' to each side of the equation.
3 + -1X + X = 7 + -1X + X

Combine like terms: -1X + X = 0
3 + 0 = 7 + -1X + X
3 = 7 + -1X + X

Combine like terms: -1X + X = 0
3 = 7 + 0
3 = 7

Solving
3 = 7

Couldn't find a variable to solve for.

This equation is invalid, the left and right sides are not equal, therefore there is no solution.

See similar equations:

| 5x+6(-2x+18)=157 | | 2(4x-3)-8=4+sx | | 7x-7-5x=19 | | h=-16t(t-5) | | 2/5-45888/2222 | | C+25=415 | | 7m=(m-4) | | -3(4-a)=-6 | | S=1/5(65-5e) | | 5x-3+3x+45=90 | | 4x-18+90=180 | | y=(x+3)(x^2+25)(x^2-2x+10) | | -3(4-a)=-15 | | -2n-12=-6(2+6n) | | 96=15+9s | | 5x+6(-2+18)=157 | | 5(n+3)=3(2*n-1) | | 8y-3y=35 | | 5x+6(-2+18)=108 | | 4y=3x+C | | 63/w=9 | | 12x=5(8+2x) | | h=-2(t-1)-16t(t-1) | | XP+to=z | | 8m+10=50 | | 4(x-5)+6=2(2x-7) | | x*5+65=4*x | | 24+5h=89 | | 10x-3/12 | | X^2-9x-19/x-2 | | 2x-54=104 | | 2(x+3)+x+7=2(3x+9)+5(4-x)+3 |

Equations solver categories